2016
DOI: 10.1177/0961203316655212
|View full text |Cite
|
Sign up to set email alerts
|

Can SLE classification rules be effectively applied to diagnose unclear SLE cases?

Abstract: Summary Objective Develop a novel classification criteria to distinguish between unclear SLE and MCTD cases. Methods A total of 205 variables from 111 SLE and 55 MCTD patients were evaluated to uncover unique molecular and clinical markers for each disease. Binomial logistic regressions (BLR) were performed on currently used SLE and MCTD classification criteria sets to obtain six reduced models with power to discriminate between unclear SLE and MCTD patients which were confirmed by Receiving Operating Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(64 reference statements)
0
2
1
Order By: Relevance
“…Although stepwise procedure generated optimal criteria combinations for predicting SLE, the strongest predictor turned out to be the overall classification, regarding both SLICC-12 and ACR-97 classification. This is contradictory to the results of Mesa at al (38), who, also employing regression analysis, reported that reduced models, rather than the whole classification, were better discriminators of SLE patients among unclear cases of MCTD. Al-Daabil et al (39) found that strong predictors of SLE were oral ulcerations, renal impairment, and anti-dsDNA antibodies.…”
Section: Discussioncontrasting
confidence: 87%
“…Although stepwise procedure generated optimal criteria combinations for predicting SLE, the strongest predictor turned out to be the overall classification, regarding both SLICC-12 and ACR-97 classification. This is contradictory to the results of Mesa at al (38), who, also employing regression analysis, reported that reduced models, rather than the whole classification, were better discriminators of SLE patients among unclear cases of MCTD. Al-Daabil et al (39) found that strong predictors of SLE were oral ulcerations, renal impairment, and anti-dsDNA antibodies.…”
Section: Discussioncontrasting
confidence: 87%
“…Efforts to refine diagnostic criteria and distinguish between SLE and MCTD are underway, with studies exploring novel molecular markers and classification criteria showing promise for improving diagnostic accuracy [ 9 ]. However, the lack of established guidelines and ongoing research highlights the need for further investigation into diagnostic methodologies and clinical presentations to enhance our understanding and management of these complex autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are much more stable than linear RNAs in cells, and in some tissues their expression levels are 10 times higher, so circRNAs could be regarded as preferred biomarkers of diseases [ 9 , 15 , 16 ]. Many SLE symptoms are quite similar to those of other illnesses, which makes it vague and difficult to diagnose [ 17 ] Currently, the diagnosis of SLE often requires presence of typical clinical manifestations combined with lab indicators [ 18 ]. In the present study, we found that 2 circRNAs (hsa_circ_0049224 and has_circ_0049220) were differently expressed in the PBMCs of healthy controls vs. inactive SLE and active patients, and patients with and without some clinical characteristics of SLE had significantly different expressions of these 2 circRNAs ( Table 2 ), which means that hsa_circ_0049224 and has_circ_0049220 may participate in the pathogenesis of SLE or even be related with the degree of disease activity.…”
Section: Discussionmentioning
confidence: 99%